COVID-19 and public actions for the urban poor - Rashid, Shahidur; Bin Khaled, Muhammad Nahian (Financial Express, 2020)
Dealing with nation-wide disruptions is nothing new to Bangladesh. Political unrest, military coups, and natural disasters in the country have time and again made global news headlines, often with sad imageries. The people of the country and its leadership have also been widely applauded for their resilience and success in managing large-scale shocks. But the lockdown under COVID-19 appears to be different. It is clearly the largest disruption of livelihoods in the country's history, with its long-term impacts far exceeding the earlier shocks, such as the 1998 floods or many episodes of tumultuous political unrest.